Pemuda dalam simpul-simpul praktikal : hasil diskusi serial DPP KNPI - Patmono Sk., 1953-; Kartika, Kristiya; Komite Nasional Pemuda Indonesia (Jakarta : KNPI, 1993)
Indonesian politics and government, Pancasila, the state philosophy of Indonesia, and youth movement in Indonesia; results of discussions.
Mode of access: Internet.
Keywords: Pancasila; Youth movements -- Indonesia; Indonesia -- Politics and government -- 1966-1998.